Study comparison P-Delta Effect analysis depends on height variation of the building - Istiono, Heri; Susanti, Eka; Propika, Jaka; Ramadhan, Azhar Yusuf (Faculty of Civil Engeneering and Planning - ITATS, 2022)
Indonesia is an area where three active plates meet, so many areas are prone to earthquakes. To anticipate this and minimize casualties due to earthquakes, earthquake-resistant buildings are needed. Earthquake resistant buildings are the most important thing that needs to be considered, a building structure must be designed to be able to withstand lateral loads such as earthquakes within the limits set by the code/standard. The result of the earthquake load will produce an additional effect on the multi-storey building, namely the P-Delta effect. In this study, the effect of these effects will be analyzed on non-rise buildings and high-rise buildings. Analysis of the P-Delta effect will be calculated on the modeling of three buildings for non-rise buildings (Building models A, B and C) and three highrise building models (Building models D, E and F) and get the results that the P-Delta Effect has an impact on changes structural performance level in Model E Building (56 meters) from Immediate Occupancy to Life Safety